The influence of PWIM and PWIM-MID on descriptive writing skills in terms of writing self-efficacy - Gusti Yarmi; Anggi Citra Apriliana; Prayuningtyas Angger Wardhani (Universitas Sebelas Maret, 2024)
The aim of this research is to obtain a comprehensive picture of the influence of the Picture Word Inductive Model (PWIM) and Picture Word Inductive Model Based on Multiliteracy, Integrative and Differentiation (PWIM-MID) on the ability to write descriptive text in terms of students' writing self-efficacy. The sample in this research was class III students at Setiabudi 01 primary school, Setiabudi subdistrict, South Jakarta City. The method used is an experiment with a 2 x 2 factorial design. The research results are as follows: 1) Learning to write descriptive text using the PWIM and PWIM-MID models is included in the quite effective category. 2) Based on the Two Ways Anova test, a sig value of 0.045 ˂ 0.05 was obtained, meaning that there was a difference in the increase in the ability to write descriptive text between students with the PWIM and PWIM-MID models. 3) Based on the Test of Between Subject Effect, a sig value of 0.424 ˃ 0.05 was obtained, students who have low writing self-efficacy do not necessarily have the ability to write low descriptive text and vice versa, students who have high writing self-efficacy do not necessarily have the ability to write high descriptive text. 4) Based on the calculation of the interaction effect, a sig value of 0.026 ˂ 0.05 is obtained, meaning that there is an interaction effect between the writing model and writing self-efficacy on increasing students' ability to write descriptive text. Based on the results obtained, it can be concluded that learning using the PWIM and PWIM-MID models is quite effective in implementing students who have different writing self-efficacy (low writing self-efficacy and high writing self-efficacy).